(untitled) (Journal of the College of Education for Women, 2019)
The Anticyclone Merge affects Iraq’s climate clearly through its impact on the different climatic elements. where it appears while they pass through special and distinctive weather . and most of this affection appears in temperatures, Therefore, this research study the relationship between the repetition and the survival period of the Anticyclone Merge and temperature average by using coefficient correlation (Pearson) that shows there’s strong inverse relationship between the integration of Anticyclones and temperatures average. Generally speaking. a state of stability and low temperatures accompanying these Anticyclones in the cold months of the year. as is the case in the transitional months where clear sky and moderate temperatures prevail. This research studies the integration of the Siberian high pressure with the European high pressure and the Siberian high with subtropical high pressure and the European high pressure with the subtropical high for the stations in Mosul. Baghdad and Basra and the period (2005-2015) and for nine months in a year, this is because in these months the Anticyclone Merge are shown. Keywords: Anticyclons .Merge .Temperature.